1987
DOI: 10.1007/bf02554789
|View full text |Cite
|
Sign up to set email alerts
|

Does local intestinal ascorbate deficiency predispose to fistula formation in Crohn's disease

Abstract: Samples of maximally diseased and adjacent macroscopically normal intestine from 52 patients undergoing surgery for Crohn's disease were analyzed for ascorbate content; 26 of the patients had intestinal fistulas and 26 did not. Ascorbate analyses were also performed on samples of normal intestine from ten control patients. Diseased intestine from both groups of patients with Crohn's disease contained significantly more ascorbate than the adjacent macroscopically normal intestine. Their diseased intestine also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1989
1989
1995
1995

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Those patients with fistulae have either lower plasma and intestinal ascorbate levels than patients without fistulae (Gerson and Fabry, 1974) or are unable to concentrate ascorbate in inflamed intestine to the same degree as patients without fistulae (Pettit and Irving, 1987). It has been suggested that a relative deficiency of ascorbate in the diseased bowel is partly responsible for the development of these fistulae (Gerson and Fabry, 1974;Pettit and Irving, 1987). The data from the current studies would suggest that such a deficiency of ascorbate may impair the capacity of intestinal smooth muscle to heal by markedly inhibiting the secretion of procollagen by these cells.…”
Section: Discussionmentioning
confidence: 99%
“…Those patients with fistulae have either lower plasma and intestinal ascorbate levels than patients without fistulae (Gerson and Fabry, 1974) or are unable to concentrate ascorbate in inflamed intestine to the same degree as patients without fistulae (Pettit and Irving, 1987). It has been suggested that a relative deficiency of ascorbate in the diseased bowel is partly responsible for the development of these fistulae (Gerson and Fabry, 1974;Pettit and Irving, 1987). The data from the current studies would suggest that such a deficiency of ascorbate may impair the capacity of intestinal smooth muscle to heal by markedly inhibiting the secretion of procollagen by these cells.…”
Section: Discussionmentioning
confidence: 99%
“…Deficient dietary intake of thiamine (vitamin B\), riboflavin (vitamin B 2 ) , and pantothenic acid is also common (20). Vitamin C deficiency in Crohn's disease has been described (21), and controversy exists as to whether abnormal tissue vitamin C levels contribute to fistula formation in Crohn's disease (22,23). Niacin (24) and biotin (25) deficiencies have also been reported in Crohn's disease.…”
Section: Water-soluble Vitaminsmentioning
confidence: 99%